خصائص السرد والتلقي في الرواية التفاعلية الزنزانة رقم 06 لحمزة قريرة - بن مرجة, حنان (كلية الأدب العربي والفنون, 2024)
- ظهر الأدب التفاعلي نتيجة للتحولات المتسارعة التي شهدتها الحياة البشرية في القرن العشرين، مما أنتج أجناسا أدبية بحلة جديدة كالرواية التفاعلية. التي أصبحت تقدم عبر وسائط إلكترونية كالشاشة الزرقاء، وباتت توظف معطيات إلكترونية متعددة يتيحها نظام النــص المتفرع كاللقطاتالمتحركةالمرفقة بالصوتوالصورة، والحركة، والموسيقى لتكونالرواية بذلكشبيهة بالفيلمالسينمائي. الذي يعطي للمتلقي مساحة تعادل أو تزيد عن مساحة المبدع الأصلي علــى مستــوى الســرد والتلقـي Interactive literature emerged as a result of the rapid transformations that human life witnessed in thetwentieth century, which produced literary genres in a new from , such as the interactive novel which was presented via electronic media such as the Blue scéen ,and began to employ multiple electronic data made avialableby the branching text system, such as animated snapshots accompaniedby sound and image, movement , and music .thus, the novel will be similar to a cinematic film , which gives the recipient a space equal to or greater than the space of the original creator at the level of narration and reception.
Keywords: رواية، تفاعــل، خصائــص، ســرد، تلـــقـي; narration, interaction, characteristics, narration, reception